A new similarity digest search strategy applied to Minutia Cylinder-Codes for fingerprint identification - Moia, Vitor Hugo Galhardo; Henriques, Marco Aurélio Amaral (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2018: Anais do XVIII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2018)
One challenging problem on the fingerprint realm is the identification of individuals over large databases, where the most similar template must be found. Approximate matching is used in digital forensic investigations to deal efficiently with large amount of data. We think it can also be used to identify similar fingerprints with compact representations and become a promising technique to speed up searches. In this paper, we explore this hypothesis and present MCC-HBFT, a new fingerprint identification strategy based on the approximate matching technique HBFT and the state-of-the-art fingerprint representation model MCC. We show how MCC-HBFT identify fingerprints and outperforms a commonly used indexing strategy in some public databases of the field.